Statistics and Measuring the Efficiency of Crime Investigation - Vári, Vince (Magyar Rendészet, 2014)
In my study I intend to present the endeavour to improve efficiency and introduce the current model for its measurement. I attempt to analyse the disadvantageous effect of linking performance measurement to statistics-based efficiency measurement on the organizational culture and work ethic of the police, thus influencing the subjective feeling of safety of the society.